Eat Prey, Live: Dictyostelium discoideum As a Model for Cell-Autonomous Defenses - Dunn, Joe Dan; Bosmani, Cristina; Barisch, Caroline; Raykov, Lyudmil; Lefrançois, Louise H.; Cardenal-Muñoz, Elena; López-Jiménez, Ana Teresa; Soldati, Thierry (Frontiers in Immunology, 2018)
The soil-dwelling social amoeba Dictyostelium discoideum feeds on bacteria. Each meal is a potential infection because some bacteria have evolved mechanisms to resist predation. To survive such a hostile environment, D. discoideum has in turn evolved efficient antimicrobial responses that are intertwined with phagocytosis and autophagy, its nutrient acquisition pathways. The core machinery and antimicrobial functions of these pathways are conserved in the mononuclear phagocytes of mammals, which mediate the initial, innate immune response to infection. In this review, we discuss the advantages and relevance of D. discoideum as a model phagocyte to study cell-autonomous defenses. We cover the antimicrobial functions of phagocytosis and autophagy, and describe the processes that create a microbicidal phagosome: acidification and delivery of lytic enzymes, generation of reactive oxygen species, and the regulation of Zn2+, Cu2+, and Fe2+ availability. High concentrations of metals poison microbes while metal sequestration inhibits their metabolic activity. We also describe microbial interference with these defenses and highlight observations made first in D. discoideum. Finally, we discuss galectins, TRAFs, TRIMs, and STATs, microbial restriction factors initially characterized in mammalian phagocytes that have either homologs or functional analogs in D. discoideum.